24h-Sodium excretion and hydration status in children and adolescents - Results of the DONALD Study - Alexy, Ute; Cheng, Guo; Libuda, Lars; Hilbig, Annett; Kersting, Mathilde (Clinical Nutrition)

Ansätze der Übergewichtsprävention durch verbessertes Trinkverhalten im Setting Grundschule - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Bundesgesundheitsblatt - Gesundheitsforschung - Gesundheitsschutz)

Fluids and children’s health. - Muckelbauer, R.; Libuda, Lars; Kersting, M. (Developing Children´s Food Products.)

Prepubertal Glucocorticoid Status and Pubertal Timing - Shi, Lijie; Wudy, Stefan A.; Buyken, Anette; Maser-Gluth, Christiane; Hartmann, Michaela F.; Remer, Thomas (The Journal of Clinical Endocrinology & Metabolism)
Context: Whether prepubertal glucocorticoid status impacts on the timing of puberty is not clear. Objective: The objective of the study was to examine the relationship between prepubertal glucocorticoid status and early or late pubertal markers, independent of adrenarchal and nutritional status. Design and Participants: Prospective cohort study of healthy Caucasian children (n = 111, 56 boys) who provided both 24-h urine samples and weighed dietary records 1 and 2 yr before the start of pubertal growth spurt [age at take-off (ATO)]. Measurements: Major urinary glucocorticoid and androgen metabolites determined by gas chromatography-mass spectrometry analysis were summed to assess daily overall cortisol (ΣC21) and adrenal androgen secretion; urinary free cortisol and cortisone measured by RIA were summed (UFF+UFE) as an indicator of potentially bioactive free glucocorticoids. Main Outcomes: The main outcomes included ATO, age at peak height velocity, age at menarche/voice break, ages at Tanner stage 2 for breast (girls) and genital (boys) development, and pubic hair. Results: In girls ΣC21, but not UFF+UFE, was associated with pubertal markers after adjusting for overall adrenal androgen, urinary nitrogen, and body fat. Girls with higher ΣC21 (fourth quartile) reached ATO 0.7 yr (P = 0.01) and menarche 0.9 yr later (P = 0.006) than girls with lower ΣC21 (first quartile). The ΣC21 tended to be also positively associated with age at Tanner stage 2 for breast (P = 0.1), Tanner stage 2 for pubic hair (P = 0.1), and age at peak height velocity (P = 0.06). In boys, neither the ΣC21 nor UFF+UFE was related to pubertal timing. Conclusion: An individually higher prepubertal glucocorticoid secretion level, even in physiological range, appears to delay early and late pubertal timing of healthy girls, particularly their onset of pubertal growth spurt and menarche.

Longitudinal associations between reported sleep duration in early childhood and the development of body mass index, fat mass index and fat free mass index until age 7 - Diethelm, Katharina; Bolzenius, Katja; Cheng, Guo; Remer, Thomas; Buyken, Anette (International Journal of Pediatric Obesity)

Consumption of polyunsaturated fatty acids, fish, and nuts and risk of inflammatory disease mortality - Gopinath, Bamini; Buyken, Anette; Flood, Victoria M; Empson, Marianne; Rochtchina, Elena; Mitchell, Paul (The American Journal of Clinical Nutrition)

Association of dietary energy density in childhood with age and body fatness at the onset of the pubertal growth spurt - Günther, Anke L. B.; Stahl, Lisa J.; Buyken, Anette; Kroke, Anja (British Journal of Nutrition)
The aim of the present study was to examine the association of pre-pubertal dietary energy density (ED) with both age and body fatness at the start of the pubertal growth spurt (age at take-off, ATO). Analyses included 219 DOrtmund Nutritional and Anthropometric Longitudinally Designed Study participants with sufficient height measurements to estimate ATO who provided 3 d weighed dietary records at baseline, i.e. 2 and 3 years before ATO (mean age 6·9 ( sd 1·2) years). Mean energy intakes and amounts of foods/drinks consumed at baseline were derived from the records. ED (kJ/g) was calculated based on (1) all foods and drinks (ED_all), (2) foods and energy-containing drinks (ED_energy), (3) foods and milk as a drink, but no other beverages (ED_milk) and (4) foods only, solid or liquid (ED_food). Using multiple regression analyses, the association between the ED variables and ATO was investigated. Furthermore, Z -scores of BMI and fat mass index (FMI) at ATO were considered as outcomes to reflect body fatness at puberty onset. The results showed that ED at baseline was not associated with ATO, regardless of the ED method used. For example, mean ATO in the lowest v. highest tertile of ED_food was 9·3 (95 % CI 9·0, 9·5) v. 9·4 (95 % CI 9·1, 9·7) years, P trend = 0·8 (adjusted for sex, maternal age, birth weight, dietary protein, dietary fibre, baseline BMI Z -score). Similarly, ED was not independently associated with BMI or FMI Z -score at ATO ( P trend = 0·3–0·9). In conclusion, dietary ED in childhood did not influence timing or body fatness at ATO in this cohort of healthy, free-living children.

Regional and socio-economic differences in food, nutrient and supplement intake in school-age children in Germany: results from the GINIplus and the LISAplus studies - Sausenthaler, Stefanie; Standl, Marie; Buyken, Anette; Rzehak, Peter; Koletzko, Sibylle; Bauer, Carl Peter; Schaaf, Beate; von Berg, Andrea; Berdel, Dietrich; Borte, Michael; Herbarth, Olf; Lehmann, Irina; et al. (Public Health Nutrition)
Abstract Objective To describe regional differences between eastern and western Germany with regard to food, nutrient and supplement intake in 9–12-year-old children, and analyse its association with parental education and equivalent income. Design Data were obtained from the 10-year follow-up of the two prospective birth cohort studies – GINIplus and LISAplus. Data on food consumption and supplement intake were collected using an FFQ, which had been designed for the specific study population. Information on parental educational level and equivalent income was derived from questionnaires. Logistic regression modelling was used to analyse the effect of parental education, equivalent income and region on food intake, after adjusting for potential confounders. Setting Germany. Subjects A total of 3435 children aged 9–12 years. Results Substantial regional differences in food intake were observed between eastern and western Germany. Intakes of bread, butter, eggs, pasta, vegetables/salad and fruit showed a significant direct relationship with the level of parental education after adjusting for potential confounders, whereas intakes of margarine, meat products, pizza, desserts and soft drinks were inversely associated with parental education. Equivalent income had a weaker influence on the child's food intake. Conclusions Nutritional education programmes for school-age children should therefore account for regional differences and parental education.

Prevention strategies for type 2 diabetes should be based on evidence-based medical nutrition data. Reply to Uusitupa M, Lindström J, Tuomilehto J [letter] - Buyken, Anette; Mitchell, P.; Ceriello, A.; Brand-Miller, J. (Diabetologia)

The glycemic index issue - Brand-Miller, Jennie; Buyken, Anette (Current Opinion in Lipidology)

Den Umgang mit Geld und Konsum lernen – Verbraucherbildung in der Schule - Schlegel-Matthies, Kirsten (Stimme der Familie)

Was ist Verbraucherbildung? – Was kann sie leisten? - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Approximative occlusion culling using the hull tree - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias (Proceedings of the Graphics Interface 2011 Conference, May 25-27, St. John's, Newfoundland, Canada)
Occlusion culling is a common approach to accelerate real-time rendering of polygonal 3D-scenes by reducing the rendering load. Especially for large scenes, it is necessary to remove occluded objects to achieve a frame rate that provides an interactive environment. In order to benefit from the culling properly, often hierarchical data structures are used. These data structures typically create a spatial subdivision of a given scene into axis-aligned bounding boxes. These boxes can be tested quickly, but they are not very precise. By using these boxes, the included objects are detected as visible, even if other objects occlude them (false-positives). To get perfect results, the models original geometry included in the box has to be tested, but this would require too much computational power. To overcome this problem, original objects approximations could be used, but typical methods for mesh simplification cannot be applied, because they do not create an outer hull for a given object. We present a model simplification algorithm, which generates simple outer hulls, consisting of only few more triangles than a box, while preserving an objects shape better than a corresponding bounding box. This approach is then extended to a hierarchical data structure, the so-called hull tree, that can be generated for a given scene to improve the visibility tests. Next, we present an approximative rendering algorithm, which combines the features of the hull tree with the use of inner hulls for efficient occlusion detection and global state-sorting of the visible objects.

Anglistische Korpuslinguistik. Eine Einführung. Grundlagen der Anglistik und Amerikanistik 33 - Mindt, Ilka; Mukherjee, Joybrato (Anglistik. International Journal of English Studies, 22, 1)

Parallel Out-of-Core Occlusion Culling - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm
We present a parallel rendering system for PC-Clusters to visualize large 3D scenes. One single visualization node, equipped with a high-end graphics adapter, is supported by a group of backend nodes with weak graphics performance. The objects of the scene are distributed among these backend nodes, they serve two purposes: First, they provide an out-of-core memory system for the visualization node. Second, they assist the visualization node's rendering by performing visibility calculations and only sending visible objects to the visualization node. In order to obtain fast rendering with our system, we have to distribute the objects among the backend nodes in a way that does not only guarantee an even distribution of the objects, but also an even distribution of the visibility calculations and the amount of data send to the visualization node. We identify necessary properties of the distribution and argue that a random distribution is a good candidate. Further, in order to reduce the number of objects sent to the visualization node per frame, we employ an approximate hierarchical occlusion culling in each backend node. For this, they are equipped, in addition to the objects assigned to them, with simplified versions of the other objects of the 3D scene. The visualization node is equipped with 512 MiB video memory and supported by 15 backend nodes. This system is able to render a approx. 350 million polygons (approx. 8.5 GiB) large aircraft model between 20 - 30 fps and thus allows a walkthrough in real-time.

Coding Opportunities from Similar Data in Wireless Cooperation Diversity Systems - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (IEEE 8th International Conference on Mobile Adhoc and Sensor Systems, MASS 2011, Valencia, Spain, October 17-22, 2011)

Ernährungssozialisation und -bildung und die Entstehung einer "kulinarischen Vernunft" - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Heindl, Ines (Die Zukunft auf dem Tisch. Analysen, Trends und Perspektiven der Ernährung von morgen)

Ernährung und Diätetik - Schlegel-Matthies, Kirsten; Methfessel, Barbara ("Gesunde Lebensführung" - kritische Analyse eines populären Konzepts)

Mahlzeit im Wandel - die Entideologisierung einer Institution - Schlegel-Matthies, Kirsten (Mahlzeiten. Alte Last oder neue Lust?)

Zyklizität und doppelte Autorschaft im Liebesfrühling von Clara und Robert Schumann - Grotjahn, Rebecca (Robert Schumann. Persönlichkeit, Werk und Wirkung. Bericht über die Internationale Musikwissenschaftliche Konferenz vom 22. bis 24. April 2010 in Leipzig)